Genetic relationship analysis of chrysanthemum genotypes based on quantitative and qualitative characters - Sanjaya, Liauw Lia; Hanudin,; Budiarto, Kurniawan; Mawaddah,; Rahardjo, Indijarto Budi; Rachmawati, Fitri; Kurniati, Ridho; Shintiavira, Herni; Indrasti, Rita; Rawung, Jefny B. Markus; Mulyono, Djoko; Suhendar, M. Ace; et al. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Genetic improvements through biotechnological approaches have been successfully employed in many economically important crops, including ornamentals. The gamma-ray particle bombardment has been applied in the chrysanthemum variety Puspita Nusantara and superior mutants has successfully generated without degrading its important marketable characteristics. The vegetative and reproductive performances of 47 superior mutant genotypes from Puspita Nusantara are evaluated and compared with three references varieties, i.e., Puspita Nusantara, Stangkon and Arosuko Pelangi based on the quantitative and qualitative characteristics. The evaluation was carried out to select superior mutants with better characteristics. The results show that all chrysanthemum genotypes exhibited variations in quantitative characteristics, except in node length, the width of the widest point of inflorescence, the number of flowers per plant, and floret width. Six qualitative characters, i.e., non-glossy leaves, medium indentation depth, the existence of keel, inner and outer floret color, disc color before anther dehiscence, and disc color after anther dehiscence were similar in all genotypes. Mutant clones G6, G8, C1, KA7, G9, AG0, N9, and Q5 show preferable quantitative performances than the reference varieties. Clone W5 has comparative characteristics to Stangkon and can be further evaluated for alternative reference. The selected mutant genotypes provide better choices for farmers to plant more competitive varieties.